Endokanibalizm – rytualny posiłek jako element kultu przodków - Żychliński, Daniel (Folia Praehistorica Posnaniensia, 2019)
This article presents the hypothesis concerning the practicing of ritual eating of dead bodies of family members by people of Wielbark culture in Wielkopolska (Greater Poland) in the Roman Period. Such practices are called as endocannibalism and this custom is connected very closely with ancestors’ worship. It is an expression of love to a dead family member and an attempt of assimilating his best features. Such a possibility is suggested by archaeological discoveries made at Wielbark culture cemeteries in Wielkopolska (Greater Poland). Endocannibalism was noticed in the past, but is also recorded in modern times.